PHYLOGENY AND EVOLUTIONARY HISTORY OF VIETNAMESE Arisaema (ARACEAE) - Van Tien, Tran; Van Du, Nguyen; Thi Van Anh, Nguyen; Chi Toan, Le (Journal of Forestry Science and Technology, 2023)
In the family Araceae, Arisaema Mart is one of the largest genera with 200 species in the world, and mainly distributed in the temperate and warm-temperate areas from the East to South-East of North America to northern Mexico, from tropical East and North-East Africa to the Arabian Penisula, and from temperate East Asia to South and South-East Asia and Malesia. Several species of Arisaema are used as food and local medicine in India, China and Vietnam. Exploring the relationship between plants and explaining where plants originated and how they migrated between regions in the world and Vietnam is still challenging. Construction of molecular phylogeny, estimations of the divergence time and ancestral area of lineages based on evidences of molecular data, fossils, geology have provided major insights into plant evolution. This study was conducted based on comprehensive taxon sampling and molecular data from four chloroplast DNA regions of Arisaema to determine the phylogeny and evolutionary history of Vietnamese Arisaema (Araceae). The phylogeny of Arisaema was studied by using ML and BI methods. Our results indicated that Arisaema originated in Southeast Asia at ca. 31 Ma during the Oligocene and that Vietnamese Arisaema was derived from the Southeast Asia Arisaema during climate optimum period of Mid-Miocene with the presence and development of the tropical rainforest. Whereas, Vietnamese Arisaema likely does not have any connection with Arisaema from India, North China, Japan and the Korean Peninsula regions.